Endogenous microbial contamination of melons (Cucumis melo) from international trade: an underestimated risk for the consumer?. (15th May 2018) - Esteban‐Cuesta, Irene; Drees, Nathalie; Ulrich, Sebastian; Stauch, Peter; Sperner, Brigitte; Schwaiger, Karin; Gareis, Manfred; Gottschalk, Christoph
Abstract: BACKGROUND: Fruits and vegetables have increasingly been related to foodborne outbreaks. Besides surface contamination, a possible internalization of microorganisms into edible parts of plants during growth has already been observed. To examine an actual risk for the consumer, microbial contamination of the rind and pulp of 147 muskmelons from international trade was assessed using cultural and biochemical methods, polymerase chain reaction and matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry. RESULTS: One hundred percent of the rind samples [3.69–8.92 log colony forming units (CFU) g −1 ] and 89.8% of the pulp samples (maximum load 3.66 log CFU g −1 ) were microbiologically contaminated. Among the 432 pulp isolates, opportunistic and potentially pathogenic bacteria were identified, mainly Staphylococcus spp. (48.9%), Clostridium spp. (42.9%) and Enterobacteriaceae (27.9%) . Salmonella spp., Escherichia coli and isolates of the Bacillus cereus group were found on the rind (1.4%, 0.7% and 42.9%, respectively) and in the pulp (0.7%, 1.4% and 4.7%). Clostridium perfringens was isolated from the rind of seven melons. CONCLUSION: The present study revealed a regularly occurring internal contamination of melons. Possible health risks for consumers because of an occurrence of microorganisms in melon pulp should be considered in future food safety assessments. © 2018 Society of Chemical Industry